2013
DOI: 10.3389/fpsyg.2013.00732
|View full text |Cite
|
Sign up to set email alerts
|

The Iowa Gambling Task in depression – what have we learned about sub-optimal decision-making strategies?

Abstract: Our earlier study found patients with depression to show a preference for larger reward as measured by the Iowa Gambling Task (IGT). In this IGT version, larger rewards were associated with even larger consequent losses. In the light of the clinical markers defining depressive disorder, this finding might appear controversial at first. Performance of depressed patients on various decision-making (DM) tasks is typically found to be impaired. Evidence points toward reduced reward learning, as well as the difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 47 publications
3
62
0
1
Order By: Relevance
“…Manic BD patients are hypersensitive to rewards (Cassidy et al, 1998). Schizophrenia patients exhibit disrupted contingency learning (Brambilla et al, 2012), whereas depressed patients are more sensitive to punishment (Adida et al, 2011;Must et al, 2013). Collectively, these findings support differing mechanisms underlying poor decision making in these disorders.…”
Section: Introductionmentioning
confidence: 86%
“…Manic BD patients are hypersensitive to rewards (Cassidy et al, 1998). Schizophrenia patients exhibit disrupted contingency learning (Brambilla et al, 2012), whereas depressed patients are more sensitive to punishment (Adida et al, 2011;Must et al, 2013). Collectively, these findings support differing mechanisms underlying poor decision making in these disorders.…”
Section: Introductionmentioning
confidence: 86%
“…In depression, there is also evidence for impaired performance on the Iowa Gambling Task (Must et al 2006(Must et al , 2013Cella et al 2010;Han et al 2012), though with some studies not finding impairment (Westheide et al 2007;Smoski et al 2008). There is also evidence of impairments in reversal learning in depression (Murphy et al 2003;Robinson et al 2012;Hall et al 2014).…”
Section: Depressionmentioning
confidence: 99%
“…It is a necessary ability for adequate functioning, and is often impaired in patients with psychiatric disorders such as schizophrenia, 1 obsessive-compulsive disorder, 2,3 bipolar disorder (BD) 4 and depression, 5 and neurological disorders such as multiple sclerosis 6 and traumatic brain injury. 7 Recent studies have also identified it as a significant predictor of clinical outcomes such as treatment dropout and relapse in substance disorders 8,9 and future substance use in patients with BD.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Most investigations of DM impairment, especially in psychiatric populations, rely on instruments designed for performance measurement, such as the Iowa Gambling Task (IGT), 16 a computerized instrument which evaluates DM under uncertainty or risk in a simulated card game. This task has been used to study DM impairments in BD, 17 major depressive disorder (MDD), 5 schizophrenia, 1 and obsessive-compulsive disorder. 18 Although these studies have made important contributions to the literature, additional measures of DM could complement these findings and perhaps address some of the limitations associated with the use of the IGT.…”
Section: Introductionmentioning
confidence: 99%